A sport federation`s attempt to restructure a coach education program using constructivist principles - Paquette, K. J.; Hussain, A.; Trudel, P.; Camire, M. (International Sport Coaching Journal, 2014)
Building on Hussain et al.`s (2012) analysis of Triathlon Canada`s constructivist-informed coach education program from the perspective of the program designer, this case study explored the structure and initial implementation of the program, as well as coaches` perspectives of their journey to certification. Through a series of document analyses and interviews with the inaugural group of coach participants (N = 4), strategies for the application of constructivist principles are presented and discussed in relation to the coaches` perspectives and coach development literature. More specifically, through its innovative use of learning activities and formative evaluation and assessment strategies, the program is shown to place considerable emphasis on coaches` biographies, reflection, and representation of learning. Finally, recommendations for coach educators are presented.